Adverse reactions of lip fillers with hyaluronic acid (Research, Society and Development, 2023)
The application of hyaluronic acid in orofacial harmonization represents a significant advancement in contemporary aesthetics and dentistry, offering a versatile and safe therapy to enhance facial aesthetics. This naturally occurring substance in the human body is employed to correct imperfections, enhance contours, and balance aesthetic proportions. However, its application requires deep anatomical knowledge and technical skill, underscoring the importance of personalized treatment for satisfactory results. When carried out by qualified professionals, the use of hyaluronic acid is safe and effective, improving facial aesthetics and patients' quality of life. Nevertheless, it is crucial to acknowledge that adverse reactions can occur, ranging from swelling and pain to more serious complications such as infections or allergic reactions. Therefore, it is imperative that professionals are aware of these possibilities, adopting preventive measures such as strict asepsis, and prepared to address contingencies. Effective communication with patients and thorough assessment are essential strategies to minimize the risk of adverse reactions, thus ensuring the safety and efficacy of orofacial harmonization procedures. Hence, the objective of this work is to present a narrative literature review on the adverse reactions of lip augmentation with hyaluronic acid.